Lactoferrin bridges antimicrobial and healing responses in Staphylococcus aureus skin infections - Kosznik-Kwaśnicka, Katarzyna; Leszczyńska, Urszula; Piechowicz, Lidia (Frontiers in Microbiology, 2026)
Staphylococcus aureus is a leading cause of skin and wound infections worldwide, with methicillin-resistant strains (MRSA) posing a persistent clinical challenge due to antibiotic tolerance and biofilm formation. Lactoferrin, an iron-binding glycoprotein abundant in mammals’ secretions and neutrophil granules, has emerged as a promising multifunctional agent that could help manage staphylococcal skin and wound infections, as it combines direct antimicrobial activity with immunomodulatory and tissue-repair effects. This mini-review aims to synthesize current evidence on the role of lactoferrin in the prevention and treatment of staphylococcal skin and wound infections, focusing on its antimicrobial mechanisms, modulation of host responses, and therapeutic applications. In vitro studies demonstrate that lactoferrin inhibits S. aureus growth through iron sequestration and membrane disruption, and it can also disrupt biofilm formation and persistence. Additionally, experiments showed that lactoferrin modulates inflammation, reduces oxidative stress, and promotes fibroblast migration and collagen deposition, facilitating wound closure. Lactoferrin incorporated into hydrogels, films, or nanocarriers enhanced antibacterial activity and synergized with antibiotics or bacteriophages in preclinical models. Nonetheless, variability in dosing, formulation, and study design limits cross-study comparisons, and potential bacterial resistance mechanisms remain underexplored. Therefore, further controlled and standardized studies are needed in order to optimize clinical translation and integration into modern wound care.